MARKETING STRATEGY IN EFFORT TO INCREASE COMPETITIVE ADVANTAGE IN SMALL AND MEDIUM ENTERPRISES - Yunita Sari; Angga Wibowo Gultom (Universitas Pakuan, 2020)
The purpose of this research was to examine the influence of product, price, distribution channel and promotion on competitive advantage in small and medium enterprises in Ogan Komering Ulu Regency. The research design was a survey research with a quantitative approach. The population in this research were small and medium enterprises in OKU Regency which are 270 people. The samples used in this study used Slovin formula. the number of samples used in this research were 73 people. The analytical method used is multiple linier regression. The conclusion of this research shows that the variables of product quality, price, distribution channel and promotion have a positive influence on the competitive advantage of small and medium enterprises in OKU Regency. The implication of this research for the company by using marketing strategy can increase competitive advantage. Whereas for The government this research can improve the economy and also reduce the unemployment rate.